СУБНАНОСЕКУНДНА КОМУТАЦІЯ ВИСОКОВОЛЬТНИХ ТРИГАТРОНІВ - Бойко, М.І. (Інститут електродинаміки НАН України, Київ, 2024)
The paper studies the mode of sub-nanosecond switching operation of trigatrons with an operating voltage of up to 1 MV. It is shown that the mode of such activation takes place because of the creation of primary volume streamer in the trigatron discharge gap under the action of a strong non-uniform electric field. The streamer occupies the entire gap and has a weak glow brightness. An estimated analytical calculation of the trigatron switching process in 0.3 ns is given. The process of sub-nanosecond breakdown of a trigatron with an operating voltage of up to 1 MV is presented. During the process the impact ionization after the incoming of a control pulse with a front of no more than 4 ns and an amplitude of 70 kV in the trigatron occurs along the entire length of the discharge gap of down to 12 mm: between the control electrode and opposing main one as well as between the control electrode and the main one covering it. The experimental data on the increase in the brightness of the discharge glow in the trigatron already after the end of the switching process are given. References 12, figures 6.